PENGARUH AGRESIVITAS PAJAK, UKURAN PERUSAHAAN, LEVERAGE, DAN ROA TERHADAP CORPORATE SOCIAL RESPONSIBILITY - Kusumo, Wahyu Kencono Rukmi Hadi; Asyik, Nur Fadjrih (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
The purpose of this research is to examine the influence of tax aggressiveness (ETR), firm size (SIZE), leverage (LEV), and return on assets (ROA) of corporate social Responsibility (CSR) to the mining companies which are listed in Indonesia Stock Exchange.The samples have been done by using purposive sampling method. The population is all mining companies which are listed in Indonesia Stock Exchange in 2012-2015 periods. 14 mining companies of 56 manufacturing companies have been acquired as samples with 4 year observations period (2012-2015). The data has been analyzed by using multiple linear regression analysis.The results of tax aggressiveness in this research means that costs which have been used for CSR program are addressed to the company to minimize the tax burden. In the firm size, large assets can be used for the costs of the CSR disclosure of the company. Leverage which is owned by the company will make the debtor, creditors, and investors require the company to seek for more information which is related to the CSR, its indicated as effort to obtain appropriate trust. The ROA which is owned by company will become the attention of stakeholders because the environmental impact which has been generated from the exploration.Keywords: tax aggressiveness, firm size, leverage, return on assets, corporate social responsibility.